Uppgradering av biogas med aska från trädbränslen - Andersson, Johan (SLU/Dept. of Energy and Technology, 2013)
The Swedish production of biogas was 1,5 TWh 2011. About half of the production was used as vehicle fuels. The cost for upgrading biogas depends on the size of the biogas plant and its gas production. If the gas flow is low the cost will be high. However, further development of existing upgrading technologies or development of new ones, have good potential to decrease the upgrading cost for small scale biogas plants. The aim of this master thesis is to investigate a new technology for upgrading biogas to vehicle fuel standards. The investigated technology is based on the carbonation principle, which means that carbon dioxide is fixed by calcium oxide under the formation of calcite. Wood ash, which is rich of calcium oxide, has been used for capturing carbon dioxide in biogas during the lab-scale tests. During the tests the composition of the ingoing biogas was 35 % carbon dioxide and 65 % methane. When the gas passes through the ash bed the carbon dioxide was fixed by the ash and that is the reason why the methane yields is about 95-100 % in the outgoing gas. Three different types of wood ashes have been investigated. They originate from combustion of wood pellets respectively different assortment of wood chips. Ash from combustion of wood pellets shows the best ability to capture carbon dioxide, 0,24 g CO2/g dry ash. A Proposal on a system design has been developed based on the results from the lab-scale tests. Simplified calculations showed that the upgrading cost for the proposed system was 0,24 kr/kWh. That is about half of the cost compared to the available small-scale upgrading technologies on the market. The calculations were based on a biogas plant with the annual gas production of 1 GWh, which is a typical size for a Swedish farm-scale biogas plant.